2011
DOI: 10.3917/drs.079.0689
|View full text |Cite
|
Sign up to set email alerts
|

Le tribunal administratif : une affaire d'initiés ? Les inégalités d'accès à la justice et la distribution du capital procédural

Abstract: Résumé Cet article met en lumière les inégalités des requérants dans les conditions d’accès au tribunal administratif. À partir de l’étude statistique d’un grand nombre de jugements, les auteurs soulignent d’abord un important effet de sélection : les cadres et professions intellectuelles (s’agissant de la fonction publique) ainsi que les artisans et chefs d’entreprise (s’agissant des litiges fiscaux) sont fortement sur-représentés devant le tribunal. Ensuite, la probabilité d’obtenir gain de cause ne dépend p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 0 publications
1
6
0
5
Order By: Relevance
“…These findings confirm those of studies on the users of ombuds institutions in other national contexts, where women have been shown to be significantly underrepresented, with some notable exceptions (Hubeau, 2018). They also confirm existing studies on access to administrative courts: in France, for instance, around two-thirds of complainants are men (Spire and Weidenfeld, 2011; Weidenfeld, 2008).
Figure 1.Comparison of gender as percentages.
…”
Section: Results Of the Studysupporting
confidence: 85%
See 1 more Smart Citation
“…These findings confirm those of studies on the users of ombuds institutions in other national contexts, where women have been shown to be significantly underrepresented, with some notable exceptions (Hubeau, 2018). They also confirm existing studies on access to administrative courts: in France, for instance, around two-thirds of complainants are men (Spire and Weidenfeld, 2011; Weidenfeld, 2008).
Figure 1.Comparison of gender as percentages.
…”
Section: Results Of the Studysupporting
confidence: 85%
“…day (Spire and Weidenfeld, 2011). They might also have more often observed that 'talking to people' is more effective than writing.…”
mentioning
confidence: 99%
“…Interestingly, we observe a more significant impact for litigated conflicts: income is a more determining factor in satisfaction with the outcome when the judge makes a decision than when a solution is found outside the courtroom. This result sheds light on the unequal experiences with the legal system (Spire and Weidenfeld, 2011): when people turn to the courts, the wealthiest respondents are much more likely to be satisfied with the legal decision than low-income respondents.…”
Section: Unequal Satisfaction With the Outcome Of The Conflictmentioning
confidence: 79%
“…In the end, except for a few taxpayers who do not know how to conduct themselves during their hearing (Spire and Weidenfeld, 2011), the only sentence that has any real significance occurs when the court declares the tax debt to be a jointly held obligation: such a characterization allows the tax authority to transfer the corporate tax debt to its director. It is as if the criminal procedure were to function in the same way as a purely administrative process, the only purpose being to recover unpaid taxes.…”
Section: Methodsmentioning
confidence: 99%